Composite positive electrode material and preparation method and application thereof

CN123017939APending Publication Date: 2026-10-30GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611305703.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明提供了一种复合正极材料及其制备方法和应用,以解决现有技术中包覆体系易分层脱落、容量快速衰减、循环稳定性差的问题来实现材料电化学性能的协同提升

Benefits of technology

1.本发明提供一种复合正极材料,通过第一包覆层提供电子导电网络、第二包覆层提供锂离子传输通道,实现电子-离子双导通,改善复合正极材料倍率性能和容量发挥;同时还利用锂离子导体中的Li+在热处理过程中部分嵌入正极表面晶格,补偿锂缺陷,主动提升复合正极材料首次库仑效率和可逆容量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a composite positive electrode material and a preparation method and application thereof, the composite positive electrode material comprises a core, a first coating layer and a second coating layer, the first coating layer is coated on the surface of the core, and the second coating layer is coated on the surface of the first coating layer; the first coating layer comprises cyclized polyacrylonitrile, and the second coating layer comprises a lithium ion conductor. + During the heat treatment process, part of the lithium ions are embedded into the surface lattices of the positive electrode, lithium defects are compensated, and the first coulomb efficiency and reversible capacity of the composite positive electrode material are actively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to a composite cathode material, its preparation method, and its application. Background Technology

[0002] Ultra-high nickel single-crystal ternary cathode materials possess a specific capacity exceeding 210 mAh / g, making them a key cathode material for next-generation high-energy-density lithium-ion batteries (especially all-solid-state lithium batteries). However, when applied to sulfide solid-state electrolyte systems, these materials face significant interfacial challenges: the narrow electrochemical window of the sulfide electrolyte readily leads to irreversible redox reactions with the high-voltage cathode material, generating a high-resistivity interfacial layer; rigid solid-solid contacts result in high interfacial impedance; and residual alkali on the cathode material surface exacerbates interfacial side reactions. Surface coating is widely recognized as the most effective strategy for addressing these interfacial problems, and various technical routes have been developed, including oxide coating, fast-ion conductor coating, conductive polymer coating, and composite coating.

[0003] Currently, coating modification technology for electrode materials has been widely studied and applied, but existing coating schemes still have unavoidable technical defects. Specifically, a single coating layer structure cannot simultaneously achieve multiple functional regulation, failing to meet various needs such as ion conduction, interface inhibition, and structural buffering, resulting in significant limitations in modified functions. While multilayer composite coating strategies can integrate multiple functional advantages, existing preparation methods struggle to establish chemical bonds between different coating layers. Interlayer bonding relies solely on physical adsorption and mechanical adhesion. During charge and discharge, the electrode material continuously expands and contracts in volume, generating cyclic stress. The weak interlayer interfaces are highly susceptible to delamination and peeling, rendering the coating protective effect ineffective. This leads to the re-triggering of numerous interfacial side reactions between the electrode and electrolyte, ultimately causing rapid capacity decay and severely limiting the long-term cycling performance of the electrode material. Summary of the Invention

[0004] This invention provides a composite cathode material, its preparation method, and its application, in order to solve the problems of easy delamination, rapid capacity decay, and poor cycle stability of the coating system in the prior art, and to achieve a synergistic improvement in the electrochemical performance of the material.

[0005] In a first aspect, the present invention provides a composite cathode material, the composite cathode material comprising a core, a first coating layer, and a second coating layer, wherein the first coating layer coats the surface of the core, and the second coating layer coats the surface of the first coating layer. The first coating layer comprises cyclized polyacrylonitrile, The second coating layer includes a lithium-ion conductor.

[0006] Cyclic polyacrylonitrile has a conjugated conductive structure, which can provide an electron transport network for electron transport. The flexible molecular chains of cyclic polyacrylonitrile can buffer the volume change of the matrix and maintain the stability of the composite cathode material structure. Meanwhile, the lithium-ion conductor can provide a fast lithium-ion transport channel and act as a rigid protective layer to isolate the electrolyte, thereby improving the stability of the electrode interface and obtaining a composite cathode material with high energy density, long cycle life and high safety.

[0007] In one alternative implementation, the doping element of the core includes at least one of zirconium and strontium; In one alternative embodiment, the first coating layer further includes a conductive agent; Optionally, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes, graphene, and acetylene black; In one alternative embodiment, the lithium-ion conductor is selected from at least one of lithium niobate, lithium borate, lithium aluminate, and lithium titanate.

[0008] In one optional embodiment, the core is lithium nickel cobalt manganese oxide, the chemical formula of which is LiNi. x Co y Mn (1-x-y) O2, 0.8≤x≤0.94, 0.03≤y≤0.1; Secondly, the present invention also provides a method for preparing the composite cathode material, comprising the following steps: S1, Polyacrylonitrile and organic solvent are mixed to obtain mixed solution A. The matrix is ​​added to mixed solution A, mixed, electrospinned and calcined to obtain intermediate; S2, the precursor solution and intermediate of the lithium-ion conductor are mixed and calcined to obtain the composite cathode material.

[0009] In one optional embodiment, the lithium niobate precursor comprises niobium ethoxide and lithium acetate, wherein the molar ratio of Li to Nb in the niobium ethoxide and lithium acetate is 1:1. In one optional embodiment, the precursor of the lithium borate comprises boric acid and lithium hydroxide, wherein the molar ratio of Li to B in the boric acid and lithium hydroxide is 3:1. In one optional embodiment, the lithium aluminate precursor comprises aluminum isopropoxide and lithium acetate, wherein the molar ratio of Li to Al in the aluminum isopropoxide and lithium acetate is 1:1 to 1.05:1; In one optional embodiment, the lithium titanate precursor comprises tetrabutyl titanate and lithium acetate, wherein the molar ratio of Li to Ti in the tetrabutyl titanate and lithium acetate is 4:5. In an optional embodiment, in step S2, the precursor solution of the lithium-ion conductor includes a lithium-ion conductor precursor and a solvent, wherein the solvent includes at least one of ethanol and water. Optionally, the solvent for the lithium niobate precursor solution is anhydrous ethanol; Optionally, the solvent of the lithium borate precursor solution is at least one of water and an ethanol-water mixed solvent; Optionally, the solvent for the lithium aluminate precursor solution is anhydrous ethanol; Optionally, the solvent for the lithium titanate precursor solution is anhydrous ethanol.

[0010] In one optional embodiment, the method for preparing the matrix includes mixing a ternary precursor, lithium hydroxide, and a dopant, and sintering them to obtain the matrix; Optionally, the dopant includes at least one of zirconium-containing compounds and strontium-containing compounds; Optionally, the sintering step includes first heating to 500-600℃ at a heating rate of 1-3℃ / min, holding at that temperature for 1-5 hours, and then heating to 800-820℃ at a heating rate of 1-3℃ / min, holding at that temperature for 8-12 hours. In an optional embodiment, step S1 further includes adding a conductive agent to the mixed solution A.

[0011] In one alternative embodiment, the amount of dopant added is 0.1-0.3% based on the mass of the ternary precursor; In one optional embodiment, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the ternary precursor is (1.02-1.05):1; In one optional embodiment, the amount of the conductive agent added is 1-10% based on the mass of polyacrylonitrile; Understandably, within this range, electron transport impedance can be further reduced and rate performance improved based on the cyclized polyacrylonitrile conductive network, but excessive addition will damage fiber formability.

[0012] In one optional embodiment, the mass ratio of the matrix to polyacrylonitrile is (5-20):1; it is understood that if the ratio is too low, the coating layer will be too thick and affect lithium-ion transport; if the ratio is too high, the coating layer will be incomplete and unable to provide protection. In one optional embodiment, the molecular weight of the polyacrylonitrile is 80,000-150,000 Da; It is understandable that too low a molecular weight will result in insufficient fiber mechanical properties, while too high a molecular weight will result in excessive solution viscosity, affecting the spinning process. In one optional embodiment, the mass concentration of polyacrylonitrile in the mixed solution A is 6%-15%; In one alternative embodiment, the amount of the lithium-ion conductor precursor added is 0.5-5% by weight of the intermediate; Understandably, too low a coating amount will prevent the formation of a complete fast ion conductor layer, while too high a coating amount will increase the resistance to lithium-ion transport. In one optional embodiment, the zirconium-containing compound includes at least one of zirconium oxide, zirconium hydroxide, zirconium nitrate, and zirconium acetate; In one optional embodiment, the strontium-containing compound includes at least one of strontium oxide, strontium hydroxide, strontium nitrate, and strontium carbonate; In one optional embodiment, the organic solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; In one optional embodiment, the lithium source includes lithium hydroxide; In one optional embodiment, in step S1, the electrospinning process parameters include a voltage of 15-30kV, a receiving distance of 10-25cm, and a feed speed of 0.5-3.0mL / h. In one optional embodiment, in step S1, the calcination temperature is 300-500°C, the calcination time is 2-6 hours, and the atmosphere is at least one of an inert atmosphere and air. In one optional embodiment, in step S1, the ball-to-material ratio of the ball mill is (5-20):1, the rotation speed is 200-600 rpm, and the ball milling time is 1-8 h; the particle size Dv50 of the intermediate after ball milling is 3-10 μm. Under these process parameters, the nanofiber membrane formed by calcination in step S1 can be broken into independent coated particles. During the high-energy ball milling process, the brittle polyacrylonitrile and conductive agent coating layers remain on the matrix surface when the fibers break, forming a complete core-shell structure powder.

[0013] In one optional embodiment, in step S2, the calcination temperature is 300-600℃, the calcination time is 2-6h, and the atmosphere is an oxygen atmosphere; by controlling the calcination temperature and time, polyacrylonitrile (PAN) is cyclized into conductive cyclized polyacrylonitrile (cPAN) while maintaining the flexibility of the fiber membrane, ensuring the integrity of the coating layer during the subsequent ball milling process. Optionally, in step S2, when the lithium-ion conductor is lithium niobate, the calcination temperature is 400-600℃; Optionally, in step S2, when the lithium-ion conductor is lithium borate, the calcination temperature is 350-500℃; In an optional embodiment, in step S2, after mixing the precursor solution and intermediate of the lithium-ion conductor, before calcination, the step further includes a solvent removal step, which includes drying the mixed solution B formed by mixing the precursor solution and intermediate of the lithium-ion conductor at 55-65°C for 4-12 hours.

[0014] Thirdly, the present invention also provides a positive electrode sheet comprising the above-mentioned composite positive electrode material.

[0015] Fourthly, the present invention also provides a lithium-ion battery comprising the above-described positive electrode.

[0016] Those skilled in the art will understand that the lithium-ion battery provided by the present invention may include structural components such as an electrolyte, a positive electrode, a negative electrode, a separator, and a casing. During the charging and discharging process, lithium ions repeatedly insert and extract between the positive and negative electrode. The electrolyte acts as a conductor between the positive and negative electrode. The separator is disposed between the positive and negative electrode, primarily to prevent short circuits between the positive and negative electrodes, while simultaneously allowing lithium ions to pass through.

[0017] As an example, the positive electrode sheet includes a positive current collector and a positive active layer. The positive current collector has two opposing surfaces in its own thickness direction, and the positive active layer is disposed on either or both of the opposing surfaces of the positive current collector. The material of the positive electrode sheet used in the lithium-ion battery of the present invention is a composite positive electrode material prepared by the preparation method provided by the present invention.

[0018] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer. The negative electrode current collector has two opposing surfaces in its own thickness direction, and the negative electrode active layer is disposed on either or both of the opposing surfaces of the negative electrode current collector. The materials, composition, and manufacturing methods of the negative electrode sheet used in the lithium-ion battery of the present invention may include any techniques disclosed in the prior art.

[0019] The material and shape of the separator used in the lithium-ion battery of the present invention are not particularly limited, and may include any technology disclosed in the prior art.

[0020] The electrolyte used in the lithium-ion battery of the present invention may also include any technology disclosed in the prior art.

[0021] This invention does not specifically limit the preparation method of lithium-ion batteries; lithium-ion batteries can be prepared using conventional preparation methods in the art. For example, positive electrode sheets, separators, and negative electrode sheets are stacked sequentially, with the separator located between the positive and negative electrode sheets. A cell is obtained through stacking or winding processes, and then the lithium-ion battery of this invention is obtained through baking, electrolyte injection, formation, and packaging.

[0022] Fifthly, the present invention provides an electrical device comprising the above-described lithium-ion battery.

[0023] It is understood that in the electrical equipment provided by the present invention, the lithium-ion battery can be used as a power source for the electrical equipment, or as an energy storage unit for the electrical equipment. The electrical equipment may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a composite cathode material that achieves dual electron-ion conduction through a first coating layer providing an electronic conductive network and a second coating layer providing a lithium-ion transport channel, thereby improving the rate performance and capacity utilization of the composite cathode material; simultaneously, it utilizes Li in the lithium-ion conductor... + During the heat treatment process, it is partially embedded in the lattice of the cathode surface to compensate for lithium defects and actively improve the first coulombic efficiency and reversible capacity of the composite cathode material.

[0025] On the one hand, the composite cathode material provided by this invention has a first coating layer that acts as an elastic interface layer, buffering the volume change stress of the cathode material during charging and discharging, and inhibiting particle cracking. The second coating layer, a lithium-ion conductor, acts as a rigid protective layer, effectively isolating the cathode material from direct contact with the solid electrolyte, inhibiting the oxidative decomposition of sulfide electrolytes and the formation of rock salt phase on the cathode surface. On the other hand, the metal ions (M) in the lithium-ion conductor and the cyano groups (-C≡N) of cyclized polyacrylonitrile undergo a coordination reaction to form MN chemical bonds, transforming the two coating layers from a simple physical stack to a chemically bonded integrated structure, fundamentally solving the problem of easy peeling between coating layers. This invention, through the synergistic effect of the double coating, can simultaneously inhibit both electrochemical and mechanical degradation mechanisms of capacity decay, solving the problems of incomplete function of a single coating layer and independent function between multiple coating layers in the prior art. It can simultaneously improve the capacity, initial coulombic efficiency, cycle stability, and rate performance of the composite cathode material.

[0026] 2. The present invention provides a method for preparing a composite cathode material. First, a mixed solution of a matrix and polyacrylonitrile is electrospun to obtain a nanofiber membrane coated with polyacrylonitrile. Then, an intermediate with uniformly coated cyclized polyacrylonitrile is obtained by calcination, cyclization, and ball milling, thereby achieving a uniform nanoscale distribution of the coating layer. During the calcination process, in addition to generating lithium-ion conductors, the metal ions in the lithium-ion conductor of the second coating layer can also undergo a coordination reaction with the cyano groups (-C≡N) in the cyclized polyacrylonitrile of the first coating layer to form MN chemical bonds. This transforms the two coating layers from a simple physical stack to a chemically bonded integrated structure, fundamentally solving the problem of coating layer peeling off in composite cathode materials. Detailed Implementation

[0027] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having” and any variations thereof in the text of this invention are intended to cover non-exclusive inclusion.

[0029] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0030] The "range" disclosed in this invention is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. This range can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this invention, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein; "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] In the description of the embodiments of the present invention, the term "and / or" is merely a description of the relationship between associated objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.

[0032] In the description of the embodiments of the present invention, the term "at least one" refers to one or more (including two).

[0033] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0034] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0035] Example 1 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the ternary precursor (Ni 0.92 Co 0.06 Mn 0.02(OH)2), LiOH, and additive (ZrO2) are mixed evenly, heated to 600℃ at a heating rate of 3℃ / min, held at that temperature for 4 hours, then heated to 820℃ at a heating rate of 2℃ / min, held at that temperature for 10 hours, and then naturally cooled to room temperature to obtain the matrix; the amount of additive added is 0.2% based on the mass of the ternary precursor; the molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor is 1.03:1; S2, polyacrylonitrile with a molecular weight of 120,000 Da was dissolved in an organic solvent (N,N-dimethylformamide) to prepare a 10% (w / w) mixed solution A. The matrix and conductive agent (carbon nanotubes) were added, and the mixture was stirred for 12 hours until uniformly dispersed. The solution was then loaded into a syringe and electrospun under conditions of 22 kV, a receiving distance of 18 cm, and a feed rate of 1.5 mL / h. After electrospinning, the solution was placed in a tube furnace and subjected to cyclization heat treatment at 3 °C / min in air atmosphere for 4 hours. The solution was then allowed to cool naturally to room temperature, shredded, and placed in a high-energy ball mill. The mixture was ball-milled at a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm for 4 hours to obtain a particle size D. v 50 is an intermediate with a particle size of 4 μm; the mass ratio of the matrix to polyacrylonitrile is 10:1; the amount of the conductive agent added is 5% based on the mass of polyacrylonitrile; S3, an intermediate was added to a lithium-ion conductor precursor solution (niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1) with a total concentration of 0.1 mol / L, and stirred for 4 h. The solvent was then evaporated at 60 °C, and the temperature was increased to 500 °C at 5 °C / min under an oxygen atmosphere and held for 4 h to obtain the composite cathode material. The amount of lithium-ion conductor added was 2% based on the mass of the intermediate.

[0036] Example 2 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that: In step S2, based on the mass of polyacrylonitrile, 3% of the conductive agent (carbon nanotubes) is replaced with 3% of the conductive agent (conductive carbon black). In step S3, the precursor solution of the lithium-ion conductor is replaced by "niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1" with "boric acid and lithium hydroxide dissolved in water at a molar ratio of Li:B=3:1" of equal concentration. The calcination temperature is 450°C and the holding time is 3 hours.

[0037] Example 3 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that: In step S2, the mass concentration of mixed solution A is 8%, the mass ratio of the matrix to polyacrylonitrile is 15:1, and electrospinning is performed under the conditions of 18kV voltage, 15cm receiving distance, and 1.0mL / h feed speed. The high-energy ball mill rotates at 300rpm and the ball milling time is 6h. In step S3, the precursor solution of the lithium-ion conductor is replaced by "niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1" with an ethanol solution of tetrabutyl titanate and lithium acetate (Li:Ti molar ratio=4:5, total concentration 0.05mol / L). The calcination temperature is 600℃ and the holding time is 5h.

[0038] Example 4 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that: In step S2, based on the mass of polyacrylonitrile, 3% of the conductive agent (carbon nanotubes) is replaced with 2% of the conductive agent (graphene). In step S3, the precursor solution of the lithium-ion conductor is replaced by an ethanol solution of aluminum isopropoxide and lithium acetate (Li:Al molar ratio = 1:1, total concentration 0.1 mol / L) instead of "niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb = 1:1". The calcination temperature is 450°C and the holding time is 3 hours.

[0039] Example 5 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the molecular weight of the polyacrylonitrile is 80,000 Da.

[0040] Example 6 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the molecular weight of the polyacrylonitrile is 150,000 Da.

[0041] Example 7 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the amount of conductive agent added is 1% based on the mass of polyacrylonitrile.

[0042] Example 8 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the amount of conductive agent added is 10% based on the mass of polyacrylonitrile.

[0043] Example 9 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the mass ratio of the matrix to polyacrylonitrile is 5:1.

[0044] Example 10 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the mass ratio of the matrix to polyacrylonitrile is 20:1.

[0045] Example 11 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the calcination temperature in step S2 is 300°C.

[0046] Example 12 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the calcination temperature in step S2 is 500°C.

[0047] Example 13 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that, in step S2, the amount of lithium-ion conductor precursor added is 0.5% based on the mass of the intermediate.

[0048] Example 14 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that, in step S2, the amount of lithium-ion conductor precursor added is 5% based on the mass of the intermediate.

[0049] Example 15 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the calcination temperature in step S3 is 600°C.

[0050] Example 16 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the ternary precursor (Ni 0.8 Co 0.1 Mn 0.1 (OH)2), LiOH, and additive (ZrO2) are mixed evenly, heated to 600℃ at a heating rate of 1℃ / min, held at that temperature for 1 hour, then heated to 800℃ at a heating rate of 3℃ / min, held at that temperature for 12 hours, and then naturally cooled to room temperature to obtain the matrix; the amount of additive added is 0.1% based on the mass of the ternary precursor; the molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor is 1.05:1; S2, polyacrylonitrile with a molecular weight of 80000 Da was dissolved in an organic solvent (N,N-dimethylformamide) to prepare a 15% (w / w) mixed solution A. The matrix and conductive agent (carbon nanotubes) were added, and the mixture was stirred for 12 hours until uniformly dispersed. The solution was then loaded into a syringe and electrospun under conditions of 15 kV, a receiving distance of 25 cm, and a propulsion speed of 0.5 mL / h. After electrospinning, the solution was placed in a tube furnace and subjected to cyclization heat treatment at 3 °C / min in air atmosphere for 2 hours. The solution was then allowed to cool naturally to room temperature, shredded, and placed in a high-energy ball mill at a ball-to-material ratio of 20:1, a rotation speed of 200 rpm, and a milling time of 8 hours to obtain an intermediate with a particle size D50 of 3 μm. The mass ratio of the matrix to polyacrylonitrile was 20:1; the amount of conductive agent added was 1% based on the mass of polyacrylonitrile. S3, an intermediate was added to a lithium-ion conductor precursor solution (niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1) with a total concentration of 0.1 mol / L, and the mixture was stirred for 4 h. The solvent was then evaporated at 60 °C, and the temperature was increased to 600 °C at 5 °C / min under an oxygen atmosphere and held for 2 h to obtain the composite cathode material. The amount of lithium-ion conductor added was 5% based on the mass of the intermediate.

[0051] Example 17 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the ternary precursor (Ni 0.94 Co 0.03 Mn 0.03 (OH)2), LiOH, and additive (SrO2) are mixed evenly, heated to 500℃ at a heating rate of 3℃ / min, held at that temperature for 5 hours, then heated to 820℃ at a heating rate of 1℃ / min, held at that temperature for 8 hours, and then naturally cooled to room temperature to obtain the matrix; the amount of additive added is 0.3% based on the mass of the ternary precursor; the molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor is 1.02:1; S2, polyacrylonitrile with a molecular weight of 150,000 Da was dissolved in an organic solvent (N,N-dimethylformamide) to prepare a 6% (w / w) mixed solution A. The matrix and conductive agent (carbon nanotubes) were added, and the mixture was stirred for 12 hours until uniformly dispersed. The solution was then loaded into a syringe and electrospun under conditions of 30 kV, a receiving distance of 10 cm, and a propulsion speed of 3.0 mL / h. After electrospinning, the solution was placed in a tube furnace and subjected to cyclization heat treatment at 300°C / min under air atmosphere for 6 hours. The solution was then allowed to cool naturally to room temperature, shredded, and placed in a high-energy ball mill at a ball-to-material ratio of 5:1, a rotation speed of 600 rpm, and a milling time of 1 hour to obtain an intermediate with a particle size D50 of 10 μm. The mass ratio of the matrix to polyacrylonitrile was 5:1. The amount of conductive agent added was 10% based on the mass of polyacrylonitrile. S3, an intermediate was added to a lithium-ion conductor precursor solution (niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1) with a total concentration of 0.1 mol / L, and the mixture was stirred for 4 h. The solvent was then evaporated at 60 °C, and the temperature was increased to 300 °C at 5 °C / min under an oxygen atmosphere and held for 6 h to obtain the composite cathode material. The amount of lithium-ion conductor added was 0.5% based on the mass of the intermediate.

[0052] Example 18 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that the conductive agent is replaced with an equal mass of polyacrylonitrile in step S2.

[0053] Comparative Example 1 This comparative example provides a composite cathode material, and the specific steps and operating parameters are as follows: The ternary precursor (Ni) 0.92 Co 0.06 Mn 0.02 The (OH)2), LiOH, and additive (ZrO2) were mixed evenly, heated to 600℃ at a heating rate of 3℃ / min, held at that temperature for 4 hours, and then heated to 820℃ at a heating rate of 2℃ / min, held at that temperature for 10 hours. The mixture was then allowed to cool naturally to room temperature to obtain the composite cathode material. The amount of the additive added was 0.2% based on the mass of the ternary precursor. The molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor was 1.03:1.

[0054] Comparative Example 2 This comparative example provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the ternary precursor (Ni 0.92 Co 0.06 Mn 0.02 (OH)2), LiOH, and additive (ZrO2) are mixed evenly, heated to 600℃ at a heating rate of 3℃ / min, held at that temperature for 4 hours, then heated to 820℃ at a heating rate of 2℃ / min, held at that temperature for 10 hours, and then naturally cooled to room temperature to obtain the matrix; the amount of additive added is 0.2% based on the mass of the ternary precursor; the molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor is 1.03:1; S2, the matrix is ​​added to a lithium-ion conductor precursor solution (niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1) with a total concentration of 0.1 mol / L, and stirred for 4 h. The solvent is then evaporated at 60 °C, and the temperature is increased to 500 °C at 5 °C / min under an oxygen atmosphere and held for 4 h to obtain the composite cathode material. The amount of lithium-ion conductor added is 2% based on the mass of the intermediate.

[0055] Comparative Example 3 This comparative example provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the ternary precursor (Ni 0.92 Co 0.06 Mn 0.02 (OH)2), LiOH, and additive (ZrO2) are mixed evenly, heated to 600℃ at a heating rate of 3℃ / min, held at that temperature for 4 hours, then heated to 820℃ at a heating rate of 2℃ / min, held at that temperature for 10 hours, and then naturally cooled to room temperature to obtain the matrix; the amount of additive added is 0.2% based on the mass of the ternary precursor; the molar ratio of Li in the lithium hydroxide to the total amount of transition metal ions in the ternary precursor is 1.03:1; S2, polyacrylonitrile with a molecular weight of 120,000 Da was dissolved in an organic solvent (N,N-dimethylformamide) to prepare a 10% (w / w) mixed solution A. The matrix and conductive agent (carbon nanotubes) were added, and the mixture was stirred for 12 hours until uniformly dispersed. The solution was then loaded into a syringe and electrospun under conditions of 22 kV, a receiving distance of 18 cm, and a feed rate of 1.5 mL / h. After electrospinning, the solution was placed in a tube furnace and subjected to cyclization heat treatment at 3 °C / min in air atmosphere for 4 hours. The solution was then allowed to cool naturally to room temperature, shredded, and placed in a high-energy ball mill. The mixture was ball-milled at a ball-to-material ratio of 10:1 and a rotation speed of 400 rpm for 4 hours to obtain a particle size D. v The composite cathode material has a thickness of 4 μm; the mass ratio of the matrix to polyacrylonitrile is 10:1; and the amount of conductive agent added is 5% based on the mass of polyacrylonitrile.

[0056] Comparative Example 4 This comparative example provides a composite cathode material, which differs from Example 1 only in that: In step S3, the precursor solution of the lithium-ion conductor (niobium ethanol and lithium acetate dissolved in anhydrous ethanol at a molar ratio of Li:Nb=1:1) is replaced with aluminum isopropoxide by mass, and the calcination temperature is 450℃. The second coating layer of the resulting composite cathode material is aluminum oxide.

[0057] Comparative Example 5 This comparative example provides a composite cathode material, which differs from Example 1 only in that: in step S2, polyacrylonitrile is replaced with an equal mass of conductive agent.

[0058] Experimental Example 1 The composite cathode materials provided in Examples 1-18 and Comparative Examples 1-5 were applied to lithium-ion batteries, and then their electrical performance was tested.

[0059] The method for preparing the lithium-ion battery includes the following steps: The composite cathode material prepared in Examples 1-18 or Comparative Examples 1-5 was used as the cathode active material and mixed with sulfide solid electrolyte Li6PS5Cl, conductive carbon black and polytetrafluoroethylene in a mass ratio of 82:15.5:2:0.5. The mixture was then rolled into a composite cathode film with a thickness of approximately 90 μm and a coating surface density of 20 mg / cm³. 2 It is punched into a positive electrode sheet with a diameter of 12mm.

[0060] The positive electrode, solid electrolyte Li6PS5Cl, lithium indium alloy negative electrode and current collector are stacked in sequence and placed in a coin cell case under an argon atmosphere in a glove box. After pressurization, the cells are sealed to obtain a CR2032 coin cell. Finally, the cells are placed in the Blue Electric CT3001 battery testing system for electrical performance testing.

[0061] The specific method for the electrical performance test is as follows: (1) First charge and discharge performance test After the open-circuit voltage stabilizes at 25°C, the battery's first charge-discharge performance is tested by cycling at 0.1C / 0.1C for one week: the initial charge capacity is defined as the capacity when the battery is charged at a constant current of 0.1C until the voltage reaches 4.3V, and the initial discharge capacity is defined as the capacity when the battery is discharged at a constant current of 0.1C until the cutoff voltage reaches 2.8V. The first-cycle coulombic efficiency (first-cycle efficiency) is then calculated.

[0062] The coulomb efficiency for the first lap is calculated as follows: First efficiency = 100% × 1st discharge specific capacity / 1st charge specific capacity.

[0063] (2) Cyclic stability test The assembled button cell battery was charged and discharged at 0.1C, 0.2C, 0.5C, and 1C once each at 2.8-4.3V, and then cycled 50 times at 1C at 2.8-4.3V. The performance calculation formula is as follows: Cyclic performance = 100% × 53rd discharge specific capacity / 4th discharge specific capacity.

[0064] The specific test results are shown in Table 1 below: Table 1 Electrical performance test data

[0065] As shown in Table 1, Examples 1-18 constructed a cyclic carbon conductive network through electrospinning, providing a uniformly dispersed substrate for subsequent lithium-ion conductive coating, ensuring good coating integrity, and achieving synergistic construction of electronic pathways and lithium-ion transport channels. The overall electrochemical performance of the composite cathode material was at a high level. Among them, Examples 2-18, which changed the type of conductive agent, molecular weight of polyacrylonitrile, ratio of matrix to polyacrylonitrile, electrospinning process parameters, cyclization heat treatment conditions, type, amount, and heat treatment temperature of lithium-ion conductive material, although some process parameters were adjusted, the coating integrity and conductivity of the conductive network fluctuated slightly, resulting in small differences in the specific capacity, rate performance, and cycle retention of the composite cathode material. However, all of them were able to form a relatively complete carbon conductive network and lithium-ion conductive coating layer, and the overall electrochemical performance of the composite cathode material was significantly better than that of the comparative examples.

[0066] In contrast, Comparative Example 1 did not undergo the subsequent processing of electrospinning to construct a conductive network and lithium-ion conductive phase coating, resulting only in the original high-nickel matrix material. It completely lacked the dual modification of the conductive network and lithium-ion conductive coating layer, and the particle surface had no effective protective layer, resulting in a complete lack of coating integrity. Consequently, the first-cycle coulombic efficiency, rate capacity, and cycle retention of the resulting composite cathode material all showed a significant decrease. Comparative Example 2 omitted electrospinning. The cyclic carbon conductive network construction step involves directly coating the matrix with a lithium-ion conductive phase. Due to the lack of dispersion and support from the carbon network, the coating layer is prone to local agglomeration, uneven coverage, and poor coating integrity. Lacking continuous conductive network support, the rate performance and cycle stability of the resulting composite cathode material are significantly inferior to those of the other examples. Comparative Example 3 omits the lithium-ion conductive phase coating process, only performing electrospinning-cyclic carbon conductive network modification. The matrix particles lack a lithium conductive protective layer, and their surfaces are directly exposed to the electrolyte. Unable to suppress interfacial side reactions through complete coating, the interfacial impedance of the resulting composite cathode material increases, leading to lower rate and cycle performance. In Comparative Example 4, the lithium-ion conductive coating phase was replaced with ordinary alumina. Although a certain coating could be formed, the material did not have lithium-ion conductivity, and the coating layer was prone to local defects. The coating integrity was insufficient, which hindered lithium-ion migration. Compared with Example 1, the rate capacity and cycle retention of the composite cathode material obtained by Comparative Example 5 were significantly reduced. In Comparative Example 5, polyacrylonitrile was replaced with a conductive agent. The electrospun cyclic carbon network structure could not be formed. The continuous carbon conductive skeleton was lacking, making it difficult to achieve uniform spreading of the coating phase. The coating integrity was destroyed, and the electronic conduction pathway was insufficient. The overall electrochemical performance of the composite cathode material obtained by Comparative Example 5 was significantly worse.

[0067] Therefore, it can be seen that the electrospinning construction of cyclic carbon conductive network can provide a uniformly dispersed substrate for subsequent coating and ensure the integrity of the lithium ion conductive phase coating. Both key steps are indispensable. They synergistically optimize electron conduction and lithium ion transport, alleviate the structural decay of high-nickel ternary materials during cycling, inhibit the erosion of particles by the electrolyte, and enable the composite cathode material to take into account high reversible capacity, high first efficiency, excellent rate performance and cycle stability.

[0068] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A composite cathode material, characterized in that, The composite cathode material includes a core, a first coating layer, and a second coating layer. The first coating layer coats the surface of the core, and the second coating layer coats the surface of the first coating layer. The first coating layer comprises cyclized polyacrylonitrile, The second coating layer includes a lithium-ion conductor.

2. The composite cathode material according to claim 1, characterized in that, The core is doped with at least one of zirconium and strontium. And / or, the first coating layer further includes a conductive agent; And / or, the lithium-ion conductor includes at least one of lithium niobate, lithium borate, lithium aluminate, and lithium titanate; And / or, the core is lithium nickel cobalt manganese oxide, the chemical formula of which is LiNi x Co y Mn (1-x-y) O2, 0.8≤x≤0.94, 0.03≤y≤0.

1.

3. The composite cathode material according to claim 2, characterized in that, The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, and acetylene black.

4. A method for preparing the composite cathode material according to any one of claims 1-3, characterized in that, Includes the following steps: S1, polyacrylonitrile and organic solvent are mixed to obtain mixed solution A, matrix is ​​added to mixed solution A, mixed, electrospinned and calcined to obtain intermediate; S2, the precursor solution and intermediate of the lithium-ion conductor are mixed and calcined to obtain the composite cathode material.

5. The preparation method according to claim 4, characterized in that, Precursors for lithium niobate include niobium ethoxide and lithium acetate; And / or, the precursors of lithium borate include boric acid and lithium hydroxide; And / or, lithium aluminate precursors include aluminum isopropoxide and lithium acetate; And / or, lithium titanate precursors include tetrabutyl titanate and lithium acetate; And / or, in step S2, the precursor solution of the lithium-ion conductor includes a precursor of the lithium-ion conductor and a solvent, wherein the solvent includes at least one of ethanol and water; And / or, the method for preparing the substrate includes mixing a ternary precursor, a lithium source, and a dopant, and sintering them to obtain the substrate; Optionally, the dopant includes at least one of zirconium-containing compounds and strontium-containing compounds; Optionally, the sintering includes the steps of first heating to 500-600℃ at a heating rate of 1-3℃ / min and holding at that temperature for 1-5 hours, and then heating to 800-820℃ at a heating rate of 1-3℃ / min and holding at that temperature for 8-12 hours.

6. The preparation method according to claim 5, characterized in that, The amount of dopant added is 0.1-0.3% based on the mass of the ternary precursor; And / or, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the ternary precursor is (1.02-1.05):1; And / or, based on the mass of polyacrylonitrile, the amount of the conductive agent added is 1-10%; And / or, the mass ratio of the matrix to polyacrylonitrile is (5-20):1; And / or, the molecular weight of the polyacrylonitrile is 80,000-150,000 Da; And / or, the mass concentration of polyacrylonitrile in the mixed solution A is 6%-15%; And / or, based on the mass of the intermediate, the amount of the precursor of the lithium-ion conductor added is 0.5-5%; And / or, the zirconium-containing compound includes at least one of zirconium oxide, zirconium hydroxide, zirconium nitrate, and zirconium acetate; And / or, the strontium-containing compound includes at least one of strontium oxide, strontium hydroxide, strontium nitrate, and strontium carbonate; And / or, the organic solvent includes at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

7. The preparation method according to claim 5, characterized in that, In step S1, the electrospinning process parameters include a voltage of 15-30kV, a receiving distance of 10-25cm, and a feed speed of 0.5-3.0mL / h. And / or, in step S1, the calcination temperature is 300-500℃, the calcination time is 2-6h, and the atmosphere is at least one of inert atmosphere and air; And / or, in step S1, after the intermediate is calcined, a ball milling step is also included; Optionally, the ball-to-material ratio of the ball mill is (5-20):1, the rotation speed is 200-600 rpm, and the ball milling time is 1-8 hours; Optionally, the particle size D of the ball-milled intermediate... v 50 is 3-10μm; And / or, step S1 further includes the step of adding a conductive agent to the mixed solution A; And / or, in step S2, the calcination temperature is 300-600℃, the calcination time is 2-6h, and the atmosphere is an oxygen atmosphere; And / or, in step S2, after mixing the precursor solution and intermediate of the lithium-ion conductor, before calcination, the step further includes a solvent removal step, which includes drying the mixed solution B formed by mixing the precursor solution and intermediate of the lithium-ion conductor at 55-65°C for 4-12 hours.

8. A positive electrode sheet, characterized in that, The composite cathode material comprising any one of claims 1-3 or the composite cathode material prepared by any one of claims 4-7.

9. A lithium-ion battery, characterized in that, It includes the positive electrode sheet as described in claim 8.

10. An electrical appliance, characterized in that, It includes the lithium-ion battery as described in claim 9.